2019
DOI: 10.1002/ppul.24484
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adherence to noninvasive ventilation in youth with Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is an X‐linked, progressive neuromuscular disorder that results in chronic respiratory insufficiency and subsequently failure requiring noninvasive ventilation (NIV). Adherence to NIV in neuromuscular disorders and related barriers are poorly described. The aim of the current study was to assess NIV adherence, adherence barriers, and identify psychosocial predictors of adherence in young boys with early DMD‐related sleep disordered breathing and recommended nocturnal NIV. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
(127 reference statements)
0
18
0
Order By: Relevance
“…Adherence is assessed on objective criteria (built-in software data) because children and caregivers tend to overestimate real adherence [148]. Adherence reported in the literature usually not covers the entire night and represents the greatest challenge for long term CPAP/NIV [14,148,[181][182][183][184][185][186][187][188]. Numerous predictors of adherence have been identified: greater self-perceived improvement in SDB symptoms [180], developmental delay (lower compliance in children with Down syndrome) [144,189] and better adherence in children with other causes of developmental delay [190,191]), gender [190], rapid acclimatization to treatment [180], technical issues [180], NIV vs CPAP [192], side effects [180], familiarity with medical treatments, understanding of the disease and its consequences [180], greater improvement in the AHI [188,193], age [184], ethnicity [184], maternal education [184], family social support [180,184], family structure [185], perception of CPAP benefits [185], family member using CPAP [14], caregiver self-reported efficacy [194], and internalizing problems [188].…”
Section: Adherencementioning
confidence: 99%
“…Adherence is assessed on objective criteria (built-in software data) because children and caregivers tend to overestimate real adherence [148]. Adherence reported in the literature usually not covers the entire night and represents the greatest challenge for long term CPAP/NIV [14,148,[181][182][183][184][185][186][187][188]. Numerous predictors of adherence have been identified: greater self-perceived improvement in SDB symptoms [180], developmental delay (lower compliance in children with Down syndrome) [144,189] and better adherence in children with other causes of developmental delay [190,191]), gender [190], rapid acclimatization to treatment [180], technical issues [180], NIV vs CPAP [192], side effects [180], familiarity with medical treatments, understanding of the disease and its consequences [180], greater improvement in the AHI [188,193], age [184], ethnicity [184], maternal education [184], family social support [180,184], family structure [185], perception of CPAP benefits [185], family member using CPAP [14], caregiver self-reported efficacy [194], and internalizing problems [188].…”
Section: Adherencementioning
confidence: 99%
“…A common indication for home CPAP in children is obstructive sleep apnea refractory to adenotonsillectomy, 18 where CPAP functions as a "splint" to maintain patency of the pharynx and upper airway, to improve airway obstruction, decrease respiratory muscle load, and reduce the work of breathing. Home NIV may also be prescribed for patients with chronic hypercapnic respiratory failure, specifically in patients with neuromuscular and chest wall disease such as children with Duchenne's muscular dystrophy 19 …”
Section: Implementation Of Niv In the Intensive Care Vs Home Nivmentioning
confidence: 99%
“…Home NIV may also be prescribed for patients with chronic hypercapnic respiratory failure, specifically in patients with neuromuscular and chest wall disease such as children with Duchenne's muscular dystrophy. 19 Clinicians caring for children on home NIV devices in the perioperative period should be comfortable using these devices, with special attention to the specific capabilities for maximum inspired fraction of oxygen (usually limited). Most devices need to be connected to a power source, although in some countries portable battery-powered devices may be available.…”
Section: Implementati On Of Niv In the Inten S Ive C Are Vs Home Nivmentioning
confidence: 99%
“…Another study evaluating NIV adherence, adherence barriers in patients with DMD using nocturnal NIV found that mask discomfort was the most commonly reported adherence barrier. The assessment of the psychosocial functioning of patients and their caregivers revealed that caregivers' barriers and child internalizing symptoms predicted lower NIV adherence, and authors recommended multidisciplinary approach to improve adherence in children ( 112 ).…”
Section: Complications and Adherencementioning
confidence: 99%